2017
DOI: 10.15171/jlms.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 200 Mm, 365 Mm and 500 Mm Fibers of Ho:YAG Laser in Transurethral Lithotripsy of Ureteral: A Randomize Control Trial

Abstract: Results: MOT and SFR were significantly different in 500 Mm laser caliber (P = 0.046, P = 0.029, respectively). There was no remarkable difference between the three groups in this regard. Conclusion: Based upon our data, the clinical potency of the Ho: YAG laser was great in all three fiber calibers. The most important results of this comparison were the significantly higher SFR with increased laser caliber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…7 Fallah Karkan et al in their study about the clinical potency of the Ho: YAG laser on ureteral stones, based on its fiber caliber, concluded that all 3 types of laser caliber (200 Mm, 365 Mm, and 500 Mm fibers) had great efficacy in stone fragmentation, however; by increasing the laser caliber, the stone-free rate would significantly increase. 8 By working with the photo-thermal mechanism, Ho: YAG laser can fragment stones into the crater and small pieces, thus; the risk of upward migration of stone Out patient 20 22…”
Section: Discussionmentioning
confidence: 99%
“…7 Fallah Karkan et al in their study about the clinical potency of the Ho: YAG laser on ureteral stones, based on its fiber caliber, concluded that all 3 types of laser caliber (200 Mm, 365 Mm, and 500 Mm fibers) had great efficacy in stone fragmentation, however; by increasing the laser caliber, the stone-free rate would significantly increase. 8 By working with the photo-thermal mechanism, Ho: YAG laser can fragment stones into the crater and small pieces, thus; the risk of upward migration of stone Out patient 20 22…”
Section: Discussionmentioning
confidence: 99%
“…4 There is a variety of modalities for stone fragmentation including ultrasonic, electrohydraulic, pneumatic lithotripsy (PL) or laser lithotripsy (LL). 5 A number of lasers have been trialed for the LL method, that the holmium: yttrium-aluminum-garnet (Ho: YAG) was the most commonly used treatment. 6 Ho: YAG laser which mostly applied in stone fragmentation procedure is a pulsed mode modality with 2100 wavelength (nm) and ≈0.5 mm tissue penetration characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Nowadays due to the development of small equipment associated with entrance of laser science to medicine, using laser for management of urolithiasis is a good choice. 8,9 Likewise, because of small size of urethra in children, transurethral approach for bladder calculi lithotripsy by laser becomes popular among urologists and some studies showed its safety and efficacy, however more data are still needed. 6,10 The purpose of this survey was to compare the results of surgical bladder stone management in our single tertiary center.…”
Section: Introductionmentioning
confidence: 99%